1987
DOI: 10.1530/jrf.0.0810471
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic properties of the myometrium of the pony mare during pregnancy

Abstract: Recordings of uterine electrical activity were made from 5 pregnant pony mares from Day 141 to 320 of pregnancy. Three types of activity were identified. Short, medium and long bursts were quantified as the percentage of time each occurred during the hour analysed and further categorized according to frequency, amplitude and duration. The uterus was most active during the early stages recorded and became increasingly quiescent after Day 240. Short-burst activity was greatest when the uterus was most quiescent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…In the present study, control mares from experiment 1 exhibited spike burst clusters for approximately 25% of the time of each recording session (11 h recording daily) until 6 days before delivery when evening activity increased to approximately 30% of the recording time. These findings are in agreement with Haluska et al (1987) who found that the myometrium is electrically active 30% of the time in the mare in late gestation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, control mares from experiment 1 exhibited spike burst clusters for approximately 25% of the time of each recording session (11 h recording daily) until 6 days before delivery when evening activity increased to approximately 30% of the recording time. These findings are in agreement with Haluska et al (1987) who found that the myometrium is electrically active 30% of the time in the mare in late gestation.…”
Section: Discussionsupporting
confidence: 93%
“…Visual assessment of myoelectrical data files that were recorded in the last 8 h of gestation showed long periods of decreased activity followed by very short, rhythmic bursts of activity. This supports the findings of Haluska et al (1987) that there is a decrease in uterine activity 2 -4 h before foaling. This period of quiescence is thought to be the time when the foal rotates from the dorso-pubic position to the dorso-sacral position.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…8,9 Internally, during this period, the mare's uterus begins more active contractions beginning at the end of the uterus near the ovary and progressing posteriorly toward the cervix. Prior to this increase, mares may demonstrate decreased activity that could last for several weeks.…”
Section: Mare Prepartum Changesmentioning
confidence: 99%
“…Might it serve a protective role during sporadic hypoxic episodes that occur during normal pregnancy? In placental mammals, transient hypoxia accompanies spontaneous uterine contractions, called contractures, and has been observed throughout gestation in large mammals [31,[41][42][43][44] and rodents [45,46] . In rabbit, contractures lasting between 4 and 5 min were recorded from day 1 of gestation and continued to term [45] .…”
Section: Ne Blunts Hypoxia-induced Bradycardiamentioning
confidence: 99%